A short history of modern philosophy : from Descartes to Wittgenstein - Scruton, Roger (Routledge, 2002)
Discover for yourself the pleasures of philosophy! Written both for the seasoned student of philosophy as well as the general reader, the renowned writer Roger Scruton provides a survey of modern philosophy. Always engaging, Scruton takes us on a fascinating tour of the subject, from founding father Descartes to the most important and famous philosopher of the twentieth century, Ludwig Wittgenstein. He identifies all the principal figures as well as outlines of the main intellectual preoccupations that have informed western philosophy. Painting a portrait of modern philosophy that is vivid and animated, Scruton introduces us to some of the greatest philosophical problems invented in this period and pursued ever since. Including material on recent debates, A Short History of Modern Philosophy is already established as the classic introduction. Read it and find out why.